Globalization and the place of difference in the market of work. Public-private divergences and convergences (Revista LIDER, 2021)
People with physical and mental disabilities', people suffering from occupational diseases, victims of work accidents, immigrant and rural workers, as well as people from ethnic minorities, such as gypsies of Romani nationality, exhibits high levels of lack of educational and professional qualifications. These weaknesses cause social disadvantages in access to the labor market and into their professional development. Although we can not generalize the degree of labour market discrimination due to these weaknesses, the truth is that breaking the clutches of exclusion and get a paid work are more difficult for those who have the stigma of being “different” and suffer the effects of preconceptions and stereotypes from others. Using a sample of 159 leaders and pertain staff from public and private organizations', this paper seeks to better understand the factors that hinder or facilitate the professional integration of the “different” in Portugal. At the same time this manuscript aims to contribute to the emergence of political and social policies that strengthen the development of practices for equal opportunities in the context of the global economy and economic crisis, in particular high rate of unemployment, such is the current situation in Portugal. High rate of unemployment tends to augment the effect of the lack of skills of the socially disfavored.